Factors Related to Pregnant Women’s Satisfaction with Antenatal Care Services at Puskesmas Purwokerto Utara II - Adisty Nur As Syfa; Yektiningtyastuti Yektiningtyastuti (UM Purwokerto Press, 2024)
Background: The maternal mortality rate is increasing along with the increasing number of pregnant women who experience health problems or even die during pregnancy. One of the causes of these health problems is the irregularity of pregnant women in antenatal care examination visits because pregnant women have unfulfilled expectations regarding satisfaction with the services they receive. Objective: to determine the correlation between satisfaction factors, which include empathy, assurance, responsiveness, facilities, reliability, and responsibility, with the satisfaction of pregnant women, and to determine the most dominant factor related to the satisfaction of pregnant women. Method: This quantitative research with a cross-sectional approach had 33 respondents. The sampling technique used consecutive sampling. The research instrument used a questionnaire, the bivariate analysis used the Spearman Rhos test, and the multivariate analysis used multiple logistic regression tests. Results: it is known that the empathy factor (p-value 0.029), the responsiveness factor (p-value 0.001), the facility factor (p-value 0.011), and the responsibility factor (p-value 0.009) have a significant correlation with the satisfaction of pregnant women, while the assurance factor (p-value 0.095) and the reliability factor (p-value 0.370), have no significant correlation with the satisfaction of pregnant women. The most dominant factor related to the satisfaction of pregnant women is the responsibility factor (p-value 0.024). Conclusion: factors significantly related to the satisfaction of pregnant women are empathy, responsiveness, facilities, and responsibility. The most dominant factor related to the satisfaction of pregnant women is the responsibility factor of health workers.